Population Pharmacokinetic Properties of Antituberculosis Drugs in Vietnamese Children with Tuberculous Meningitis - Panjasawatwong, Navarat (Antimicrob Agents Chemother, 2020)
Optimal dosing of children with tuberculous meningitis (TBM) remains uncertain and is currently based on the treatment of pulmonary tuberculosis in adults. This study aimed to investigate the population pharmacokinetics of isoniazid, rifampin, pyrazinamide, and ethambutol in Vietnamese children with TBM, to propose optimal dosing in these patients, and to determine the relationship between drug exposure and treatment outcome. A total of 100 Vietnamese children with TBM were treated with an 8-month antituberculosis regimen. Nonlinear mixed-effects modeling was used to evaluate the pharmacokinetic properties of the four drugs and to simulate different dosing strategies. The pharmacokinetic properties of rifampin and pyrazinamide in plasma were described successfully by one-compartment disposition models, while those of isoniazid and ethambutol in plasma were described by two-compartment disposition models. All drug models included allometric scaling of body weight and enzyme maturation during the first years of life. Cerebrospinal fluid (CSF) penetration of rifampin was relatively poor and increased with increasing protein levels in CSF, a marker of CSF inflammation. Isoniazid and pyrazinamide showed good CSF penetration. Currently recommended doses of isoniazid and pyrazinamide, but not ethambutol and rifampin, were sufficient to achieve target exposures. The ethambutol dose cannot be increased because of ocular toxicity. Simulation results suggested that rifampin dosing at 50 mg/kg of body weight/day would be required to achieve the target exposure. Moreover, low rifampin plasma exposure was associated with an increased risk of neurological disability. Therefore, higher doses of rifampin could be considered, but further studies are needed to establish the safety and efficacy of increased dosing.